Downshifting to care: The role of gender and care in reducing working hours and consumption. Issue 114 (August 2020) - Lane, Ruth; Arunachalam, Dharmalingam; Lindsay, Jo; Humphery, Kim
Highlights: Reduced paid working hours of 40–59 year-olds is shaped by gender and carer roles. Home ownership facilitates reducing paid work hours to perform unpaid care. Consumption after reducing working hours is influenced by income and location. A complex gendered relationship links environmental and social welfare concerns. Abstract: The relationship between working hours and sustainability has attracted research attention since at least the early 2000s, yet the role of care giving in this context is not well understood. Focusing on Australians between 40 and 60 years who have reduced their working hours and income, we explore the relationship between working hours, care giving and consumption. Data from the national census (ABS, 2006, 2011, 2016c ) were analysed to contextualise patterns in paid working hours, income and carer roles for men and women aged between 40 and 60 years. Findings from a national survey on informal carers (ABS, 2016a ) were also consulted. Taken together, the two sources of national data showed that two thirds of all informal carers are women, that the likelihood of assuming informal carer roles increases with age, and that men and women in carer roles work fewer paid hours per week and have a lower weekly income than non-carers of the same age. To gain qualitative insights into these patterns in Australian national data, and the likely implications of carer roles for household consumption, semi-structured interviews were conducted with ten households who subsequently recorded details of their consumption-related expenses over a seven-day period. The interview data showed the strong connection between carer roles, reduced income and paid working hours and its strongly gendered dimension. We argue that women primarily 'downshift' to undertake care rather than for sustainability motivations and that there is consequently a need to connect scholarship on gender and care with that on downshifting. The link between reducing paid working hours, care-giving and household consumption appeared to be less straight forward and varied between households. Our findings suggest that a complex relationship exists between environmental and social welfare concerns that has policy implications and warrants further exploration.